A Topography of Virtual Influencers - Berryman, Rachel; Abidin, Crystal; Leaver, Tama (2021)
Informed by my first six months of doctoral research, this paper offers a topography of virtual influencers that at once acknowledges their continuation of and breaking with the precedents of a lineage of “virtual beings” who have achieved celebrity status. Responding to the ahistoricism of much recent commentary, it draws on archival press and web research to situate virtual influencers at the intersection of technological advancements, discourses, and anxieties similarly characterising Hollywood’s “synthespians” at the turn of the twenty-first century; the legacy of “virtual idols” in East Asia (also known as “Vocaloids” in Japan); and the latter’s recent democratisation by a new generation of “vTubers” across video-sharing sites. Recognising this cross-medium migration of virtual celebrity—from anime, video games and blockbuster cinema to the participatory web—this paper adopts a platform-specific lens to highlight the affordances, cultures and vernaculars of specific social media as essential to virtual influencers’ aspiration to, and attainment and maintenance of, attention and fame.